Is the Whole World Watching? Building a Typology of Protest Coverage on Social Media From Around the World. (17th August 2020) - Harlow, Summer; Kilgo, Danielle K.; Salaverría, Ramón; García-Perdomo, Víctor
ABSTRACT: Previous research suggests that mainstream media coverage around the world follows a "protest paradigm" that demonizes protesters and marginalizes their causes. Given the recent increase in global protest activity and the growing importance of social media for activism, this paper content analyzes 1, 438 protest-related English and Spanish news stories from around the world that were shared on social media, examining framing, sourcing, and marginalizing devices across media outlet type, region, language, and social media platform in order to create a typology of how the protest paradigm operates in an international and social media context. Results showed type of protest, location of protest, and type of media outlet were significantly related to whether news stories adhered to the protest paradigm. Social media shares were predicted by region of media outlet, English-language media, and type of protest.